Moving to despair? Migration and well-being in Pakistan - Chen, Joyce J.; Kosec, Katrina; Mueller, Valerie (Elsevier, 2019)
Internal migration has the potential to substantially increase incomes, especially for the poor in developing countries, and yet migration rates remain low. We evaluate the impact of internal migration on both objective and subjective measures of well-being using a unique longitudinal study in rural Pakistan spanning 1991–2013. We account for selection using covariate matching. Migrants have roughly 35–40 percent higher consumption, yet are less likely to report being happy, calm and/or in excellent health, and more likely to report having been sick recently. Our results suggest that deteriorating physical health coupled with feelings of stress and relative deprivation underlie the disparity between objective and subjective well-being. Thus, despite substantial monetary gains from migration, people may be happier and less mentally distressed by remaining at home. If traditional market mechanisms cannot reduce psychic costs, it may be more constructive to address regional inequality by shifting production – rather than workers – across space.